Predictive modeling, geographic distribution and conservation status of Tomopeas ravus Miller, 1900 (Chiroptera, Molossidae) - Loaiza Salazar, Christian R. (2017)
Tomopeas ravus, known as blunt - eared bat, is known only from thirteen confirmed localities in Peru and is currently listed as Endangered (B2 ab (iii)) by the IUCN. The distribution, occurrence extension and home range of this species is not have been completely clarified. We presents the first predictive model based on the known records and the first geographic approach to this species. On the basis of thirteen confirmed records we built a habitat model of maximum entropy determining previously the most important environmental variables for the model. An acceptable predictive index (0.970) was obtained for the final model. We determined the areas of major probability of occurrence for this species and felt the geographic distribution through the method of the polygon mínimum convex (PMC). The priority area identified for the conservation of this species is located in the northern of Peru, between the Departments of Tumbes and Piura. We recommended to use the present model as a useful tool for future evaluations of conservation of this species.